The effect of plant growth regulators on micropropagation of Melientha suavis Pierre. and assessment of genetic fidelity of regenerants based on iPBS and SRAP markers - THANAPOOM SIRINGAM; ONGKARN VANIJAJIVA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Siringam T, Vanijajiva O. 2023. The effect of plant growth regulators on micropropagation of Melientha suavis Pierre. and assessment of genetic fidelity of regenerants based on iPBS and SRAP markers. Biodiversitas 24: 4628-4634. Melientha suavis Pierre, a significant deciduous edible plant species with high nutritional value and belonging to the Opiliaceae family, holds paramount importance for both agricultural and conservation purposes in its native Southeast Asia. However, the species faces challenges due to habitat fragmentation and negative anthropogenic impacts, leading to a decline in its population. This study aimed to explore the effects of various concentrations of plant growth regulators (cytokinin and auxin) on the shoot and root development of M. suavis, and to assess the genetic stability of micropropagated plants obtained from nodal explants. In vitro shoot regeneration and proliferation were conducted on Murashige and Skoog (MS) semi-solid medium, supplemented with 6-benzylaminopurine (BAP) or kinetin (Kn) at different doses. The optimal shoot length, shoot number, and leaf volume were observed in the modified MS medium with 1.0 mg/L BAP after an 8-week incubation period. Efforts to enhance the rooting of micropropagated shoots included the addition of auxins, such as ?-naphthalene acetic acid (NAA) or indole-3-butyric acid (IBA). However, the species exhibited recalcitrant behavior during the reproduction and rooting stages, as the rooting percentage did not correlate with the increase in auxin concentration. Interestingly, the highest root number and length were achieved in the MS medium without plant growth regulators after 8 weeks of incubation. To ensure genetic fidelity, regenerants were subjected to inter-primer binding site (iPBS) and sequence-related amplified polymorphism (SRAP) marker analysis. The results revealed no genetic variation between the micropropagated plants and the mother trees, confirming the production of genetically stable progeny. Overall, this protocol presents a promising alternative for profitable propagation and establishment of genetically constant progeny of M. suavis, with important implications for sustainable applications and germplasm conservation in Southeast Asia. Addressing the challenges faced by this valuable species through micropropagation and genetic fidelity assessment can contribute significantly to its preservation and utilization for agricultural and conservation initiatives.